Balance board training: prevention of traumatic injuries of the lower extremities in female soccer players? A prospective randomized intervention study - Soderman, K.; Werner, S.; Pietila, T.; Engstrom, B.; Alfredson, H. (Knee surgery, Sports Traumatology. Arthroscopy, 2000)
This prospective randomized intervention investigated whether training on a balance board could reduce the amount of traumatic injuries of the lower extremities in female soccer players. A total of 221 female soccer players from 13 different teams playing in the second and third Swedish divisions volunteered to participate in the study. Seven teams (n = 121) were randomized to an intervention group and six teams (n = 100) to a control group and were followed during one outdoor season (April-October). Before and after the season muscle flexibility and balance/postural sway of the lower extremities were measured in the players. There were no significant differences in age, height, weight, muscle flexibility and balance/postural sway of the lower extremities between the intervention and the control group. During the season the players in the intervention group performed a special training program consisting of 10-15 min of balance board training in addition to their standard soccer practice and games. After a 37% drop-out the intervention group consisted of 62 players and the control group of 78 players. The results showed no significant differences between the groups with respect either to the number, incidence, or type of traumatic injuries of the lower extremities. The incidence rate of "major" injuries was higher in the intervention group than in the control group. Four of five anterior cruciate ligament injuries occurred in the intervention group, which means that we could not prevent severe knee injuries in female soccer players with balance board training. However, among the players who had been injured during the 3-month period prior to this investigation there were significantly more players from the control group than from the intervention group who sustained new injuries during the study period.